Studi Aspek Healing Environment Dalam Desain Interior Kafe - Damayanti, Rully; Sunyoto, Shane Frederick; Leksono, Stephanie Grace; Tjandra, Catherine Leonora; Nata, Winona Cheyenne; Winarto Oei, Andini Dwiana (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Currently, the cafe is a place to relieve stress through a healing concept in its interior design. So, the cafe design must be as comfortable as possible to meet the concept goals. This research aims to determine user perception of the healing environment in a cafe environment based on three aspects (the five basic senses, user psychology, and indoor and outdoor natural elements) and was conducted using quantitative research methodology. Data retrieval was carried out through Google Forms media using closed-ended questions. The results proved that three aspects of the healing environment, including sensory, psychological, and natural aspects described in lighting, color tone selection, air, a good level of privacy, and the presence of plants, could help the healing process. If there is one aspect that is lacking, then visitors cannot feel healing. If a café wants to create a healing environment, then the three aspects (senses, psychological, and natural) must be fulfilled.